Evolutionary trends in RuBisCO kinetics and their co-evolution with CO2 concentrating mechanisms - Íñiguez Moreno, Concepción; Capó-Bauçà, Sebastià; Niinemets, Ülo; Stoll, Heather; Aguiló-Nicolau, Pere; Galmés, Jeroni (Wiley, 2020)
RuBisCO-catalyzed CO2 fixation is the main source of organic carbon in the biosphere. This enzyme is present in all domains of life in different forms (III, II, and I) and its origin goes back to 3500 Mya, when the atmosphere was anoxygenic. However, the RuBisCO active site also catalyzes oxygenation of ribulose 1,5-bisphosphate, therefore, the development of oxygenic photosynthesis and the subsequent oxygen-rich atmosphere promoted the appearance of CO2 concentrating mechanisms (CCMs) and/or the evolution of a more CO2-specific RuBisCO enzyme. The wide variability in RuBisCO kinetic traits of extant organisms reveals a history of adaptation to the prevailing CO2/O2 concentrations and the thermal environment throughout evolution. Notable differences in the kinetic parameters are found among the different forms of RuBisCO, but the differences are also associated with the presence and type of CCMs within each form, indicative of co-evolution of RuBisCO and CCMs. Trade-offs between RuBisCO kinetic traits vary among the RuBisCO forms and also among phylogenetic groups within the same form. These results suggest that different biochemical and structural constraints have operated on each type of RuBisCO during evolution, probably reflecting different environmental selective pressures. In a similar way, variations in carbon isotopic fractionation of the enzyme point to significant differences in its relationship to the CO2 specificity among different RuBisCO forms. A deeper knowledge of the natural variability of RuBisCO catalytic traits and the chemical mechanism of RuBisCO carboxylation and oxygenation reactions raises the possibility of finding unrevealed landscapes in RuBisCO evolution.
Keywords: Enzimas -- Análisis; Enzimas - Cinética; Algas -- Fisiología; Rubisco catalysis; Carbon-concentrating mechanisms; CO2 fixation; Photosynthesis; Algae; Bacteria; Archaea; Plants; Carbon isotopic fractionation; Autotrophy